2013
DOI: 10.1179/1476830513y.0000000098
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different fructose loads on insulin sensitivity, inflammation, and PSA-NCAM-mediated plasticity in the hippocampus of fructose-fed male rats

Abstract: The results showed that long-term consumption of 10% fructose solution induces hippocampal insulin resistance and inflammation, with no concomitant plasticity changes. Interestingly, rats fed with higher concentrations of fructose displayed impaired plastic response of the hippocampus, coinciding with augmented glucocorticoid signalling, which may provide a basis for cognitive deficits associated with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…Our findings are agreement with earlier reports that that combined supplementation of phenolic compounds have more potentials than individual treatment [45] [46]. Hyperglycemia is known to be one of the vital factors that can induce expression of inflammatory biomarkers during diabetes via oxidative stress pathways and associated rise in inflammatory path to induce neural cells death and dysfunction [47] [48]. Present findings obviously show the association between inflammation and the development of DN while the levels of pro-inflammatory biomarkers such as TNF-α, Il-1β and IL-6 were Data expressed as mean ± SD (n = 6).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are agreement with earlier reports that that combined supplementation of phenolic compounds have more potentials than individual treatment [45] [46]. Hyperglycemia is known to be one of the vital factors that can induce expression of inflammatory biomarkers during diabetes via oxidative stress pathways and associated rise in inflammatory path to induce neural cells death and dysfunction [47] [48]. Present findings obviously show the association between inflammation and the development of DN while the levels of pro-inflammatory biomarkers such as TNF-α, Il-1β and IL-6 were Data expressed as mean ± SD (n = 6).…”
Section: Discussionsupporting
confidence: 93%
“…14,34 Moreover, diabetic-associated over expression of inflammatory biomarkers is recognised to provoke neural cells death and dysfunction. 35,36 Present data revealed that, NG Figure 5 Effects of naringenin (NG) on sciatic nerve activities of SOD, CAT, GPx and GR in diabetic rats. Data were expressed as Mean 6 SEM (n 5 6) and analysed using one-way ANOVA followed by Student Newman-Keuls as post hoc test.…”
Section: Discussionmentioning
confidence: 97%
“…Increased levels of inflammatory molecules are considered to be produced as a result of hyperglycemia and insulin resistance in diabetes (40,41). In addition, the diabetes-associated overexpression of inflammatory biomarkers is known to provoke neural cell dysfunction and death (42,43). Previous studies have indicated that Gs extract may exert a protective effect against inflammation (44,45).…”
Section: Discussionmentioning
confidence: 99%